Business ethics - Paliwal, Manisha (New Age International, 2006)
Business ethics is nothing but the application of ethics in business. It is the application of general ethical rules to business behavior. Business ethics concentrate on moral standards as they are applied to business policies, institutions and behaviour. It is a specialized study of moral rights or wrongs. It is a systematic study of ethical matters pertaining to business industry or related activities. In any organization from top executive to bottom-line employees, ethics is considered as every body business. It is not just only achieving high level of economic performance but also to conduct one of business?s most important social challenges, ethically at the same time. Ethics in business and management is gaining momentum day by day.